Foreign inflows and growth challenges for African countries: An intertemporal general equilibrium assessment - Diao, Xinshen; Breisinger, Clemens (International Food Policy Research Institute, 2010)
Foreign inflows are important sources of income that many African governments use to finance public investments and to support the development of manufacturing or export-oriented service sectors. Yet the recent growth experience of many African economies shows that domestic-oriented industry (construction, utilities) and services have become the largest sectors. Using Ghana and its newly found oil as an example, we analyze the dynamic relationship between increasing foreign inflows and economic growth and structural change by developing a multisector intertemporal general equilibrium model. We find that the sudden increase in petrodollars used to finance either the government's recurrent spending or public investment generates a substantial short-run growth shock consistent with the Dutch disease theory. Opposed short-run effects on the growth of the tradable and nontraded sectors lead the structure of the economy to become more domestic oriented. The creation of an oil fund helps reduce the negative growth and structural effect, while in the longer term, if oil spending does not enhance productivity, growth declines and the GDP share of the nontraded sector further increases. Smart use of oil revenue thus not only involves the creation of an oil fund but also spending inflows on productivity-enhancing investment. Whether public investments can help overcome Dutch disease effects also depends on the growth magnitude of the inflows. At the same level of investment-to-productivity-growth efficiency, public investments take longer to overcome the negative growth effects the higher the growth rate of inflows. This paper further shows that the structural effect of foreign inflows on economic development is a long-term challenge for Africa. The domestic-oriented economic structure can become a persistent phenomenon for countries that continue to receive foreign inflows in the form of petrodollars or in any other form.